Three-dimensional approach to understanding the relationship between the Plio-Quaternary stress field and tectonic inversion in the Triassic Cuyo Basin, Argentina - Giambiagi, Laura Beatriz (2015)
The Cacheuta sub-basin of the Triassic Cuyo Basin is an example of rift basin inversion contemporaneous to the advance of the Andean thrust front, during the Plio-Quaternary. This basin is one of the most important sedimentary basins in a much larger Triassic NNW-trending depositional system along the southwestern margin of the Pangea supercontinent. The amount and structural style of inversion is provided in this paper by a three-dimensional approach to the relationship between inversion of rift-related structures and spatial variations in late Cenozoic stress fields. The Plio-Quaternary stress field exhibits important N-S variations in the foreland area of the southern Central Andes, between 33 and 34° S, with a southward gradual change from pure compression, with σ1 and σ2 being horizontal, to a strike-slip type stress field, with σ2 being vertical. We present a 3-D approach for studying the tectonic inversion of the sub-basin master fault associated with strike-slip-reverse to strike-slip faulting stress regimes. We suggest that the inversion of Triassic extensional structures, striking NNW to WNW, occurred during the Plio-Pleistocene in those areas with strike-slip-reverse to strike-slip faulting stress regime, while in the reverse faulting stress regime domain they remain fossilized. Our example demonstrates the impact of the stress regime on the reactivation pattern along the faults.